(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation: This article examines the evolution of dictionaries from their traditional, physical form to their digital counterparts. It delves into the advantages and limitations of digital dictionaries, showcasing how they have changed the landscape of language learning, accessibility, and lexicography. The article highlights the key benefits of digital dictionaries, such as their accessibility, interactivity, comprehensiveness, and dynamic updates, while also acknowledging their limitations, including overreliance, potential accuracy issues, technological dependence, and the lack of tactile experience. Furthermore, the article explores the future of digital dictionaries, predicting the increasing integration of artificial intelligence (AI), augmented reality (AR), and virtual reality (VR) technologies. It envisions a future where digital dictionaries become more personalized, engaging, and comprehensive, utilizing multimodal approaches and interactive learning environments. It also highlights the article's focus on the changing landscape of language learning and lexicography, as well as the potential impact of emerging technologies.